Radiation Sensitivity and Tumor Susceptibility in ATM Phospho-Mutant ATF2 Mice - Li, Shuangwei (SAGE Publications, 2010)
The transcription factor ATF2 was previously shown to be an ATM substrate. Upon phosphorylation by ATM, ATF2 exhibits a transcription-independent function in the DNA damage response through localization to DNA repair foci and control of cell cycle arrest. To assess the physiological significance of this phosphorylation, we generated ATF2 mutant mice in which the ATM phosphoacceptor sites (S472/S480) were mutated (ATF2(KI)). ATF2(KI) mice are more sensitive to ionizing radiation (IR) than wild-type (ATF2 (WT)) mice: following IR, ATF2(KI) mice exhibited higher levels of apoptosis in the intestinal crypt cells and impaired hepatic steatosis. Molecular analysis identified impaired activation of the cell cycle regulatory protein p21(Cip/Waf1) in cells and tissues of IR-treated ATF2(KI) mice, which was p53 independent. Analysis of tumor development in p53(KO) crossed with ATF2(KI) mice indicated a marked decrease in amount of time required for tumor development. Further, when subjected to two-stage skin carcinogenesis process, ATF2(KI) mice developed skin tumors faster and with higher incidence, which also progressed to the more malignant carcinomas, compared with the control mice. Using 3 mouse models, we establish the importance of ATF2 phosphorylation by ATM in the acute cellular response to DNA damage and maintenance of genomic stability.